The effect of maximal physical exercise on relationships between the growth hormone (GH) and insulin-like growth factor 1 (IGF-1) and transcriptional activity of CYP1A2 in young ice hockey players - Kochanska-Dziurowicz, A. A.; Janikowska, G.; Bijak, A.; Stanjek-Cichoracka, A.; Mazurek, U. (The Journal of Sports Medicine and Physical Fitness, 2015)
BACKGROUND: The maximal physical exercise influences on changes in GH, IGF-1 concentrations and activity of CYP1A2. The aim of this study was to answer the question whether the change of endogenous GH and IGF-1 influenced the expression of CYP1A2 and whether these changes correlate with others parameters of blood and test.